Family Communication Patterns in Preventing Child Sexual Abuse in Binjai City, North Sumatra Province - Riani, Lia; Mazdalifah; Kurniawati, Dewi (Talenta Publisher, 2025)
The purpose of this research is to analyze Family Communication Patterns in Preventing Child Sexual Abuse in Binjai City, North Sumatra Province. The theories used in this research are interpersonal communication, family communication, and child sexual abuse which are relevant to the research conducted by researchers. The research method used in this research is descriptive research method with a qualitative approach. . The informants of this study were six families with the criteria of parents / guardians who have daughters / sons who live in Damai Village, North Binjai District, Binjai City, have never been recorded as perpetrators of sexual violence or victims of sexual violence and live in the same house with their children. The results showed that in preventing sexual violence against children, families in Damai Village, North Binjai District, Binjai City carried out a balanced split pattern of communication. The forms of messages used in preventing child sexual abuse are informative and persuasive. Factors that make family communication effective in preventing child sexual abuse in Kelurahan Damai are the surrounding environment. The local government actively educates the community about the prevention of sexual violence against children and the high level of concern of the surrounding community for child protection, which can be seen from the existence of self-help movements such as the Anak Damai Mengaji movement, the Al-Ma'un Orphan Care Community, and the last one is forming a women's case assistance team. The main obstacle to family communication in preventing sexual violence against children is psychological noise. They tend to feel taboo talking about things related to sexuality between fathers and daughters or mothers and sons. Keywords: Communication Patterns, Family, Sexual Violence